2018
DOI: 10.1038/s41598-018-22420-8
|View full text |Cite|
|
Sign up to set email alerts
|

A smartphone app to reduce excessive alcohol consumption: Identifying the effectiveness of intervention components in a factorial randomised control trial

Abstract: Our aim was to evaluate intervention components of an alcohol reduction app: Drink Less. Excessive drinkers (AUDIT> =8) were recruited to test enhanced versus minimal (reduced functionality) versions of five app modules in a 25 factorial trial. Modules were: Self-monitoring and Feedback, Action Planning, Identity Change, Normative Feedback, and Cognitive Bias Re-training. Outcome measures were: change in weekly alcohol consumption (primary); full AUDIT score, app usage, app usability (secondary). Main effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(151 citation statements)
references
References 59 publications
(56 reference statements)
7
142
1
1
Order By: Relevance
“…The outcomes of these trials show that mobile cognitive-task based interventions are feasible but not efficacious as in a stand-alone context (58,61). However, the combination of cognitive bias modification (approach bias re-training) and normative feedback significantly reduces weekly alcohol consumption in excessive drinkers (59).…”
Section: Cognitive Assessment Approaches In Sud Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of these trials show that mobile cognitive-task based interventions are feasible but not efficacious as in a stand-alone context (58,61). However, the combination of cognitive bias modification (approach bias re-training) and normative feedback significantly reduces weekly alcohol consumption in excessive drinkers (59).…”
Section: Cognitive Assessment Approaches In Sud Researchmentioning
confidence: 99%
“…Similarly, influencing the immediate dynamic relationship between cognition and drug use has also been used for intervention purposes. Web and smartphone platforms have been used to administer cognitive-task based interventions, such as cognitive bias modification (CBM) training (59)(60)(61), where cognitive performance is routinely measured as a central element of interventions that span several weeks. The outcomes of these trials show that mobile cognitive-task based interventions are feasible but not efficacious as in a stand-alone context (58,61).…”
Section: Cognitive Assessment Approaches In Sud Researchmentioning
confidence: 99%
“…A detailed description of the content, development and factorial trial evaluation of the app is reported in two separate papers 1,22 .…”
Section: Interventionsmentioning
confidence: 99%
“…Abstract: "reminded insensitive but tended" are you able to provide any BF for this statement? ; The relevant BFs for this conclusion are included in the results section of the abstract and we have added the BF range for the two-way interactive effects: "Data were mainly insensitive but tended to support there being no large main effects of the enhanced version of individual components on consumption (0.22 [1]. Bayesian analyses, more generally, are often used in clinical trials for dose finding, efficacy monitoring, toxicity monitoring, and for diagnosis/decision making [2].…”
Section: This Is a Very Good Point Made By Both Reviewers That We Do mentioning
confidence: 99%
“…One, targeting internet help-seekers with harmful levels of alcohol use (15 or more drinks/week), did not find any effects over 6 months, although some benefit appeared to occur among those who actually downloaded the app (23). A fourth smartphone app, Drink Less, evaluated among adult help-seekers with at least hazardous alcohol use who all downloaded the app, showed declines in alcohol use over time among all participants, where self-monitoring and feedback combined led to use of more app sessions (24); secondary analysis using Bayes factors showed weak evidence for an interactive combined effect of four components (normative feedback, cognitive bias retraining, self-monitoring and feedback, and action planning) yielding lower alcohol consumption (25).…”
Section: Introductionmentioning
confidence: 97%